Infections developing in patients undergoing liver transplantation: Recipients of living donors may be more prone to bacterial/fungal infections - Yamazhan, Tansu; Bulut Avşar, Cansu; Zeytunlu, Murat; Taşbakan, Meltem; Sertöz, Rüçhan; Zeytinoğlu, Ayşın; Aydemir, Şöhret; Ünalp, Ömer; Ergün, Orkan; Uğuz, Alper; et al. (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Despite surgical advances in liver transplantation and effective prophylactic strategies, posttransplant infections are the most important cause of morbidity and mortality. Diagnosis and management of infections because of developing immunosuppression is difficult and adversely affects mortality. This study aimed to review bacterial and fungal infections in patients after liver transplantation and to reveal the resistance rates. Materials and Methods: A total of 107 patients who underwent liver transplantation between January 2017 and February 2018 were evaluated retrospectively with regard to demographic characteristics, causes of transplantation, conditions that may lead to infection, postoperative infections, pathogens, and resistance patterns. Results: Of the 107 patients who underwent liver transplantation, 48 (44.8%) had an infection. Bacterial infections were detected in 41% of the patients, and fungal infections were found in 13%. When we compared living and cadaveric transplants in terms of infection development, these rates were found to be 53% and 33%, respectively (p=0.034). No statistically significant results could be obtained when evaluating conditions such as sex, presence of underlying primary disease, Model for End-Stage Liver Disease MELD score, diabetes status, total parenteral nutrition, and risk factors for infection. Conclusion: After liver transplantation, infections are often seen in the first month of the postoperative period. Knowing the most common pathogens and resistance states in this process reduces infection-related deaths by providing appropriate treatment regimens at the right time.